Method and the machine for training the running speed - Petrescu, T.-D.; Ionescu Bondoc, D. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2019)
Former sprint runner, I was particularly concerned withsprint training methodology.In this regard, I have experimented together with our training colleagues, an exercise that stimulates the increase of speed of the steps in speed running, using an installation made by our own coach, designed to stimulate and increase the frequency of the steps, coaching the so-called "super-speed".In orderto increase the running speed, besides developing motor skills, a series of technical objectives must be achieved through training.It is known that using run-on exercises, similar to running on a downhill slope, there is a series of positive influences on the kinetics of the running speed of which the impulse angle and the orientation of the impulse vector in the CGM on -the impulse angle is primordial, along with: -achieving the optimum ratio between the frequency and the length of the steps; -increasing the power released by the impulse foot; -decreasing the impulse angle; -increasing the frequency of the treadmills achieved per unit of time; -increasing the length of the steps. Our experiment has attempted to justify this kind of exercise in speed training. Finally, it was found that this exercise positively affects the last two goals listed above.